Taxonomic notes on the antlion genus Dendroleon Brauer, 1866 (Neuroptera, Myrmeleontidae, Dendroleontinae) from China, with description of a new species and a newly recorded species - Zheng, Yuchen; Hayashi, Fumio; Liu, Xingyue (Zootaxa, 2022)
A new antlion species of the genus Dendroleon Brauer, 1866 (Myrmeleontidae: Dendroleontinae: Dendroleontini), namely Dendroleon laiyanae sp. nov., from Southwest China and Northern Vietnam is described. Besides, D. regius (Navás, 1914), a rare species of Dendroleon is first recorded in China with a detailed re-description. A discussion on the diagnostic characters of Dendroleon is also provided.